Мета та завдання забезпечення національної безпеки і оборони України - Нестеренко, О. В.; Nesterenko, O. V. (Право.ua. - 2018. - № 3. - С. 205-209, 2018)
У статті обґрунтовується значимість постановки мети та завдань у сфері публічного управління. Аналізуються та узагальнюються теоретико-правові підходи до визначення мети і завдань забезпечення національної безпеки і оборони України. Визначається мета забезпечення національної безпеки і оборони України, яка полягає у створенні всіх необхідних умов для досягнення (або відновлення) та утримання стану захищеності державного суверенітету, територіальної цілісності, демократичного конституційного ладу, прав і свобод людини і громадянина, та інших національних інтересів України від реальних та потенційних загроз, усунення чи мінімізація їх деструктивного впливу на сфери воєнної, зовнішньополітичної, державної, економічної, інформаційної, екологічної безпеки, кібербезпеки України тощо.

The article substantiates the importance of setting goals and objectives in the field of public administration. Theoretical and legal approaches to determining the goals and objectives of national security and defense of Ukraine are analyzed and summarized. The goal of ensuring the national security and defense of Ukraine, which is to create all necessary conditions for achieving (or restoring) and maintaining the state of protection of state sovereignty, territorial integrity, democratic constitutional order, human and civil rights and freedoms, and other national interests of Ukraine from real and potential threats, elimination or minimization of their destructive impact on the spheres of military, foreign policy, state, economic, information, environmental security, cyber security of Ukraine, etc. It is emphasized that the achievement of this goal involves the implementation of a number of tasks to ensure national security and defense of Ukraine, namely: 1) formation, monitoring and improvement of adequate to today's challenges regulatory framework governing national security and defense of Ukraine; 2) development and implementation of a systematic, consistent and sound state policy in the field of national security and defense, focused on the effective protection of national interests; 3) creation of the optimal infrastructure of public administration and the system of subjects of national security and defense of Ukraine; 4) establishment of management, coordination and interaction in the system of subjects of national security and defense of Ukraine, and other tasks.

В статье обосновывается значение постановки целей и задач в сфере публичного управления. Анализируются и обобщаются теоретико-правовые подходы к цели и задачам обеспечения национальной безопасности и обороны Украины.
Keywords: національна безпека; оборона; мета; завдання; забезпечення; national security; defense; purpose; tasks; provision; национальная безопасность; цель; задачи; обеспечение